Entry and exit strategies in the power generation sector - Csapi, Vivien; Mohácsi, Bernadett (Marketing & Menedzsment, 2019)
Motivated by the controversies and debates, this paper attempts to address the entry and exit strategies in the power generation sector, with a special focus on entering into a renewable power generation market, or leaving a traditional market. First we summarize the trends that shape the demand and supply side of the market, than describe possible market entry barriers, reasons of exit, and finally, introduce the existing strategies. Upon examining electrical energy projects, the planning of electrical energy composition, which can contain both entry and exit decisions, one has to deal with a problem complex from multiple aspects. The difficulties arise from the particularities of investments in the sector (irreversibility, uncertainty, long lifetime), moreover the features of the sector itself (numerous players with varying preferences and risk attitudes, changing regulatory and market environment, the special nature of electric power as a product) and all this things result in the complexity of entry and exit related decision making (Csapi 2013). But what makes the market so unpredictable, so risky and still worth to enter? Internationalization is what covers almost every aspect of human life, including politics, culture, science, financial systems and lifestyles. This increasing cross-border flow of capital and goods from different countries has fostered globalization. Trade liberalization, production internationalization, and financial and technological saturation are the major drivers behind what shapes the power generation sector today. Now, we try to summarize those trends that affect a company’s future strategy, development and innovation process, and influence product and technology planning..